Clinical and endocrine characteristics and genetic analysis of Korean children with McCune–Albright syndrome: a retrospective cohort study. Issue 1 (December 2016) - Cho, Eun-Kyung; Kim, Jinsup; Yang, Aram; Ki, Chang-Seok; Lee, Ji-Eun; Cho, Sung; Jin, Dong-Kyu
Abstract Background McCune–Albright syndrome (MAS) is a rare disease defined by the triad of fibrous dysplasia (FD), café au lait spots, and peripheral precocious puberty (PP). Because of the rarity of this disease, only a few individuals with MAS have been reported in Korea. We describe the various clinical and endocrine manifestations and genetic analysis of 14 patients with MAS in Korea. Methods Patients' clinical data—including peripheral PP, FD, and other endocrine problems—were reviewed retrospectively. In addition, treatment experiences of letrozole in five patients with peripheral PP were described. Mutant enrichment with 3′-modified oligonucleotides - polymerase chain reaction (MEMO-PCR) was performed on eight patients to detect mutation inGNAS using blood. MEMO-PCR is a simple and practical method that enables the nondestructive selection and enrichment of minor mutant alleles in blood. Results The median age at diagnosis was 5 years 2 months (range: 18 months to 16 years). Eleven patients were female, and three were male. Thirteen patients showed FD. All female patients showed peripheral PP at onset, and three patients subsequently developed central PP. There was a significant decrease in estradiol levels after two years of letrozole treatment. However, bone age was advanced in four patients. Two patients had clinical hyperthyroidism, and two patients had growth hormone (GH) excess with pituitary microadenoma. c.602G > A (p.Arg201His) inGNAS was detected in two patients in blood, and c.601C > T (p.Arg201Cys) inGNAS was detected in one patient in pituitary adenoma. Conclusions This study described the various clinical manifestations of 14 patients with MAS in a single center in Korea. This study first applied MEMO-PCR on MAS patients to detectGNAS mutation. Because a broad spectrum of endocrine manifestations could be found in MAS, multiple endocrinopathies should be monitored in MAS patients. Better treatment options for peripheral PP with MAS are needed.